Current challenges in molecular diagnostics of insect venom allergy - Perez-Riverol, A. [UNESP] (2020)
Background: Advanced component-resolved diagnostics (CRD) in Hymenoptera venom allergy (HVA) has improved the precise description of individual sensitization profiles. However, diagnostic gaps, peptide-based cross-reactivity, early identification of severe reactors and diagnosis of patients with a clear history of sting reactions but negative specific IgE and skin tests, remain challenging. Methods: Systematic literature search in PubMed and critical analysis of recently published studies on insect venom allergy diagnostics. Results and discussion: CRD has increased the sensitivity of IgE testing and improved the discrimination of primary sensitization from irrelevant cross-reactivity, ultimately providing a better rationale for therapeutic decisions. Despite these major advances, there is still room for improvement in routine HVA diagnostics. Peptide based cross-reactivity among homologous allergens from Vespinae and Polistinae venoms as well as still existing diagnostic gaps are particularly challenging. No marker allergens are currently available to differentiate Vespula and Polistes sensitizations. Several strategies including clinical setting of basophil activation test (BAT) for routine diagnostics, venomic analysis for the identification of novel allergens and characterization of the molecular basis of cross-reactivity could be used to address major limitations and unresolved issues in molecular diagnostics of HVA.